2019
DOI: 10.3847/1538-4357/aafe10
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Photochemistry of Covalently Bonded Fluorene Clusters: Observation of an Interesting PAH Bowl-forming Mechanism

Abstract: The fullerene C 60 , one of the largest molecules identified in the interstellar medium (ISM), has been proposed to form top-down through the photo-chemical processing of large (more than 60 Catoms) polycyclic aromatic hydrocarbon (PAH) molecules. In this article, we focus on the opposite process, investigating the possibility that fullerenes form from small PAHs, in which bowl-forming plays a central role. We combine laboratory experiments and quantum chemical calculations to study the formation of larger PAH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…25 For this reason, several recent studies have been focusing on PAH pentagon formation schemes, to further exploit bowling mechanisms under interstellar conditions. 26,27 With the tenuous connection between PAHs and fullerenes in space, it is worth noting that fullerenes may contribute to the ionization balance of the ISM and the photoelectric heating of PDRs in a similar way as PAHs have been found to be. 28 In and of itself C 60 has been proposed as a diagnostic tool to estimate the temperature and/or UV flux inside molecular clouds 29 but such data is dependent on measurements of solid C 60 rather than gas-phase measurements as those relative to DIBs studies.…”
Section: Introductionmentioning
confidence: 98%
“…25 For this reason, several recent studies have been focusing on PAH pentagon formation schemes, to further exploit bowling mechanisms under interstellar conditions. 26,27 With the tenuous connection between PAHs and fullerenes in space, it is worth noting that fullerenes may contribute to the ionization balance of the ISM and the photoelectric heating of PDRs in a similar way as PAHs have been found to be. 28 In and of itself C 60 has been proposed as a diagnostic tool to estimate the temperature and/or UV flux inside molecular clouds 29 but such data is dependent on measurements of solid C 60 rather than gas-phase measurements as those relative to DIBs studies.…”
Section: Introductionmentioning
confidence: 98%
“…Also, Carpentier et al (2012) found disordered, "fullerene-like structures" in soot particles emulating HACs, while Duley & Hu (2012) suggested the presence of "protofullerenes" in Raman spectra of HAC analogs, but neither experimental study claimed evidence of C 60 in their data. Laboratory work by Tielens and collaborators (e.g., Berné & Tielens 2012;Zhen et al 2014;Zhang et al 2019) suggests that PAHs may be a route to C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have reported laboratory experiments on van der Waals bonded, PAH clusters and their photochemical evolution towards large PAH molecules in a bottom-up process (Zhen et al 2018;Zhang et al 2019). Given the presence of C 60 in PDRs such as NGC 7023 (Sellgren et al 2010), studies of clusters involving C 60 have become of great interest as well.…”
mentioning
confidence: 99%